The Vanished Pantheon: The Attempt to Establish a Burial Site for the Nation’s Cultural Giants during the State’s First Decade (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
This article discusses the attempt to establish a pantheon for the great cultural figures of the Jewish people on Jerusalem’s Har HaMenuchot during Israel’s early years. I examine the idea of creating a national burial site designated for the country’s intellectuals – writers, poets, and thinkers – which would serve as a national memorial institution. It was intended to resemble pantheons for cultural giants in other countries, such as Poets’ Corner in Westminster Abbey in London. The attempt was not successful. The initiative was intended to commemorate the contributions of intellectuals – including Peretz Smolenskin, Avraham Shalom Yahuda, Naftali Herz Imber, Zvi Hermann Schapira, and Joseph Klausner – to shaping Zionist national identity. The first stage explored the idea of establishing a pantheon in the Nicanor Cave on Mount Scopus, but this idea was abandoned due to opposition from university authorities and the fluidity of borders during the War of Independence. After the establishment of the state, Mount Herzl served as the national burial site for politicians and fallen soldiers, and in addition, a special section on the summit of Har HaMenuchot was designated for cultural figures. I identify four main reasons for the project’s failure: legal and bureaucratic barriers; ideological disputes centering on the relationship between religion and state; competition from existing pantheons such as Mount Herzl, the Kinneret cemetery, and the old Tel Aviv cemetery on Trumpeldor Street; and the secondary status of intellectuals in the state’s early years. Although the idea was abandoned, the section designated for it on Har HaMenuchot became the burial place of Jerusalem’s distinguished citizens. This local solution achieved recognition from the city but did not achieve national recognition. I show that institutional and social conflicts reflect the tension between collective and state memory and that the fate of the intellectuals mirrored their status in the national culture of the period.
Keywords: burial; burial societies; Har HaMenuchot; Jerusalem; nationalism; pantheon